Navigating nostalgia and hope: Metamodern oscillation in Tracy K. Smith’s Life on Mars - Mariwan Hasan (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2025)
This study examines Tracy K. Smith’s Life on Mars as a representative example of metamodernist literature, focusing on the dynamic interplay of nostalgia, hope, and emotional complexity. The research asks: How does Smith’s poetry embody the oscillation between postmodern irony and modernist sincerity? In what ways do nostalgia and hope function as metamodern strategies for addressing contemporary social and existential challenges? Through a close reading of selected poems, the paper demonstrates that Smith’s work reflects a metamodern sensibility, balancing despair and longing with resilience and imaginative renewal. The findings suggest that Life on Mars portrays nostalgia as a critical, reflective mode rather than mere sentimentality, while hope emerges as a transformative force enabling readers to navigate uncertainty and envision collective connection.